Ransom kidnapping in Italy: crime, memory, and violence - Montalbano, Alessandra (Toronto Italian studies, 2024)
"For over thirty years, modern Italy was plagued by ransom kidnapping perpetrated by bandits and organized crime syndicates. Nearly 700 men, women, and children were abducted from across the country between the late 1960s and the late 1990s, held hostage by members of the Sardinian banditry, Cosa Nostra, and the 'Ndrangheta. Subjected to harsh captivities and psychological abuse, the victims spent months and even years in isolation while law enforcement and the state struggled to find them. "Ransom Kidnapping in Italy" examines this Italian criminal phenomenon. Alessandra Montalbano argues that abduction is a key vantage point from which to understand modern Italy: it troubled the law, terrified society, ignited juridical and parliamentary debates, and mobilized citizens. Bringing together archival and media materials with victims' accounts and diverse forms of cultural response, the book examines ransom kidnapping through the lenses of historiography, law, literary criticism, trauma studies, phenomenology, and political philosophy. "Ransom Kidnapping in Italy" traces how and at what price Italians became aware of living in a country that was being blackmailed by criminal organizations and arguably jeopardizing the country even more than terrorism.